Fuzzy Quantitive Strategic Planning Matrix dalam Perencanaan Strategi Perguruan Tinggi - Wulandari, Fera Tri; Widiyanto, Ibnu (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
The strategic plan helps the college in determining the direction of the college to achieve a desired future and provides a framework for achieving competitive advantage. In the strategic planning process, the selection of strategies is essential if universities do not have the resources to implement all the strategies. FQSPM designed to determine the relative attractiveness of each alternative strategy using triangular fuzzy numbers. Merger FQSPM and FTOPSIS used in the decision-making process on strategic planning by a college to conduct the election strategy based on the results of internal and external analysis. The results of the strategic planning helps colleges determine the direction to achieve the desired future so that colleges can anticipate environmental changes and predict the risk while continuing to adjust the action with the aim to be achieved college. Keywords: Strategic Planning; SWOT; Fuzzy QSPM; Fuzzy TOPSIS